Prevalence of the Most Frequent Neuropsychiatric Diagnoses in Hospitalized SARS-CoV-2 Patients Evaluated by Liaison Psychiatry: Cross-Sectional Study - Fernandes, Luis Afonso (2022)
Introduction: The SARS-CoV-2 infection has been associated with the acute onset of mental and behavioural symptoms and psychiatric disorders. The aim of this study was to assess the prevalence of the different neuropsychiatric diagnoses in hospitalized patients with SARS-CoV-2 infection assessed by Liaison Psychiatry.Material and Methods: We performed a cross-sectional study in a hospital near Lisbon, Portugal. We reviewed the electronic health records from all inpatients with a positive SARS-CoV-2 RT-PCR test that were assessed by the Liaison Psychiatry Unit (LPU) between February and December 2020. We reviewed relevant sociodemographic and clinical data, including 15 neuropsychiatric symptoms. The prevalence of psychiatric disorders was our main outcome. We also explored differences between two groups: patients with delirium (delirium group) and patients without delirium (no delirium group).Results: We included 46 cases [Age: median = 67 years; interquartile range (IQR) = 24)], with 60.9% male individuals. Delirium was the most frequent diagnosis in our sample (43.5%), followed by major depressive disorder (21.7%). Patients with delirium were more likely to suffer from COVID-19 symptoms (delirium: 19/20, 95%; no delirium: 14/26, 53.8%; p = 0.02), and to have a longer time interval between a positive SARS-CoV-2 RT-PCR test and an evaluation by the LPU (delirium: median = 16.5 days, IQR = 16; no delirium: median = 8 days, IQR = 16.3; p = 0.045). Agitation (52.2%) and cognitive symptoms (47.8%) were the most reported neuropsychiatric symptoms.Conclusion: We found a high prevalence of delirium in our sample. This finding is in line with recent literature concerning hospitalized COVID-19 patients The higher frequency of COVID-19 symptoms found in the delirium group suggests a possible association between symptomatic SARS-CoV-2 infection and delirium onset.